Study on the determination of nominated subcontractor / Mohd Izwan Shah Fadzil - Shah Fadzil, Mohd Izwan (2003)
In a construction industry there are various problems that may arise. Due to this findings, two important document was introduced namely PAM 98 and PWD 203, where it gives a guide to how contract works are done and carried out and to ensure all parties benefit the same. A study was made on this topic and the findings were, with the introduction of both form has benefited both parties namely the main contractor and the nominated subcontractor. If this is not taken into account project may be delayed and this will require extra expanses with this finding even if there is a dispute between the main contractor and subcontractor. It can be resolved due to these clauses in the contract document and with this finding all parties would be very careful in making any mistake during construction works. The findings also indicates that main contractor has the right to terminate any subcontractor due to default of any manner. The findings also indicates that the subcontractor is also able to demand extra payment if the works does not follow the existing contract. Overall these findings have made all parties to bided to the contract document and with great caution.